Contributions of attachment theory and research: A framework for future research, translation, and policy. (17th December 2013) - Cassidy, Jude; Jones, Jason D.; Shaver, Phillip R.
Abstract: Attachment theory has been generating creative and impactful research for almost half a century. In this article we focus on the documented antecedents and consequences of individual differences in infant attachment patterns, suggesting topics for further theoretical clarification, research, clinical interventions, and policy applications. We pay particular attention to the concept of cognitive "working models" and to neural and physiological mechanisms through which early attachment experiences contribute to later functioning. We consider adult caregiving behavior that predicts infant attachment patterns, and the still-mysterious "transmission gap" between parental Adult Attachment Interview classifications and infant Strange Situation classifications. We also review connections between attachment and (a) child psychopathology; (b) neurobiology; (c) health and immune function; (d) empathy, compassion, and altruism; (e) school readiness; and (f) culture. We conclude with clinical–translational and public policy applications of attachment research that could reduce the occurrence and maintenance of insecure attachment during infancy and beyond. Our goal is to inspire researchers to continue advancing the field by finding new ways to tackle long-standing questions and by generating and testing novel hypotheses.